·

Expanding single brackets

- Remember to multiply all the terms inside the bracket by the term immediately in front of the bracket.
If there is no term in front of the bracket, multiply by 1 or -1.

For I/GCSE Mathematics, you may try out the following questions below!

- 3(a - 4) = 3a - 12
6(2c + 5) = 12c + 30

- (4a + 2) = -4a - 2

8 - 2(t + 5) = -2t - 2

2p(3p + 2) - 5(2p - 1) = 6p

^{2}- 6p + 5

If you have any question, you can

Expanding double brackets

- Split the double brackets into 2 single brackets and then expand each bracket and simplify.
If a single bracket is squared [e.g. (a + 5)

^{2}] change it into double brackets (a + 5)(a + 5).

For I/GCSE Mathematics, you may try out the following questions below!

- (c + 2)(c + 6) = c
^{2}+ 8c + 12 (3a – 4)(5a + 7) = 15a

^{2}+ a – 28(p + 2)(7p – 3) = 7p

^{2 }+ 11p – 6(c + 7)

^{2}= c^{2 }+ 14c + 49(4g – 1)

^{2}= 16g^{2}– 8g + 1

That's the end!